Racial differences in pathways to care preceding first episode mania or psychosis: a historical cohort prodromal study - Gardea-Resendez, Manuel; Ortiz-Orendain, Javier; Miola, Alessandro; Fuentes Salgado, Manuel; Ercis, Mete; Coombes, Brandon J.; Gruhlke, Peggy M.; Bostwick, J. Michael; Michel, Ian; Vande Voort, Jennifer L.; Ozerdem, Aysegul; McKean, Alastair; et al. (Frontiers in Psychiatry, 2023)
There is evidence suggesting racial disparities in diagnosis and treatment in bipolar disorder (BD) and schizophrenia (SZ). The purpose of this study is to compare psychiatric diagnoses and psychotropic use preceding a first episode of mania (FEM) or psychosis (FEP) in racially diverse patients. Using a comprehensive medical records linkage system (Rochester Epidemiology Project, REP), we retrospectively identified individuals diagnosed with BD or SZ and a documented first episode of mania or psychosis. Illness trajectories were characterized as the time from first visit for a mental health complaint to first episode. Pathways to care preceding FEP/FEM were compared based on subsequent incident case diagnosis (BD or SZ) and self-reported race (White vs. Non-White). A total of 205 (FEM= 74; FEP= 131) cases were identified in the REP. Duration of psychiatric antecedents was significantly shorter in non-White patients, compared to White patients (2.2±4.3 vs. 7.4±6.6 years; p <.001) with an older age at time of first mental health visit (15.7±6.3 vs. 11.1±6.0 years; p= .005). There were no significant differences by race in FEM pathways to care. Overall non-White patients had lower rates of psychotropic use. These data are unable to ascertain reasons for shorter duration of psychiatric antecedents and later age of seeking care, and more broadly first age of initial symptom presentation. If symptoms are confirmed to be earlier than first time seeking care in both groups, it would be important to identify barriers that racial minorities face to access timely psychiatric care and optimize early intervention strategies.